Managerial ownership, firm size, financial performance, and corporate environmental disclosure - Amalia Rizki, Diana Oktafianti, (Opción, 2020)
This research aimed to analyze the effects of managerial ownership, firm size, and financial performance to the Corporate Environmental Disclosure. The research samples were determined by applying purposive sampling method. In this research, the utilized indicators in measuring the environmental disclosure were the environmental disclosure standards on the Global Reporting Initiative (GRI). The research results stated that the managerial ownership and firm size (total assets) caused positive effects to the corporate environmental disclosure, while the financial performance measured by the ROA demonstrated negative effects of the corporate environmental disclosure.